CARGO TRANSPORT ON THE EXAMPLE OF A SELECTED MODE OF TRANSPORT IN POLAND - Elżbieta MACIOSZEK (Scientific Journal of Silesian University of Technology. Series Transport)
The article presents the problem of the cargo transport with the example of a selected mode of transport in Poland. The volume of goods transported by air transport in 2010-2021 was analysed. Cargo transport in air transport is very popular. From year to year, there is an increase in the volume of transported goods. The coronavirus pandemic, and the related economic crisis did not significantly affect cargo transport, as was the case with passenger transport, the number of which decreased significantly during the pandemic.